Study on harmonic characteristics and optimization of multi-stage magnetic valve controllable reactor. (September 2019) - Li, Qingbo; Zhang, Dandan; Chen, Junqin; Yang, Ruilin
Abstract: This paper proposes a multi-stage magnetic valve controllable reactor based on the traditional magnetic valve controllable reactor (MCR). According to the structural characteristics of multi-stage magnetic valve, the mathematical model of harmonic characteristics of multi-stage MCR device is established, and the cross-section parameters of each magnetic valve are optimized by immune algorithm. The results show that after the number of magnetic valve stages exceeds 3, the optimization of total harmonics is reduced, and both are lower than the national common harmonic standard. Finally, the established mathematical model is verified by simulation. The results show that the three-stage and above magnetic valve structure can control the harmonic current under the national standard. The four-stage MCR can suppress the harmonics well and improve the power quality input to the distribution network.